Structural and Surface Morphology Studies of La0.67Ba0.33(Mn1−xAlx)O3 Thin Films Prepared by Sol-Gel Method. (31st March 2013) - Abdullah, H.; Zulfakar, M. S.
Abstract : Nanocrystalline thin films of La0.67 Ba0.33 (Mn 1 − x Al x )O3 (x = 0.00, 0.05, 0.10, and 0.15) were prepared by sol-gel method, as a starter material consisting of La2 O3, BaNO3, Mn(NO3 ), and Al(NO3 ). The molarities of La2 O3 and BaNO3 are constant, while molarities of Mn(NO3 ) and Al(NO3 ) were calculated based on stoichiometric theory. Thin films were deposited on quartz glass substrate by using spin coating technique and sintered at 700°C. X-ray diffractometer (XRD) patterns showed that these thin films consist of pure La0.67 Ba0.33 (Mn 1 − x Al x )O3 phase where the most prominent peak is observed at (104). All the samples display a rhombohedral structure. Scanning electron microscopy (SEM) showed that aggregation of small particles occurred more in doped films than in undoped films. The surface morphology has been studied by using AFM, and the roughness of thin films was analyzed.